Comparison and validation of three process simulation programs during warm start-up procedure of a combined cycle power plant. (1st March 2020) - Bany Ata, Ammar; Alobaid, Falah; Heinze, Christian; Almoslh, Adel; Sanfeliu, Antonio; Epple, Bernd
Highlights: Dynamic simulation model of sub-critical, three-pressure-stage HRSG is developed using PPSD. All process, automation and electrical components of the real power plant are modelled. Model validation during warm start-up procedure is carried out. A comparison between PPSD, Apros, and Aspen Plus Dynamics is performed. Abstract: The energy market is one of the largest and most important markets around the world. Where flexibility and efficient operation in the start-up of combined cycle power plants (CCPPs) play an essential role in the competitiveness of CCPPs in the energy market. Moreover, to study the CCPPs, the Dynamic simulation is suitable tool for predicting the behavior of power plant with high accuracy. In this paper, we study the details of warm start-up procedure of CCPP, with subcritical, natural circulation and three-pressure stages heat recovery steam generator. Examining the capability of Power Plant Simulator & Designer (PPSD) by validating the numerical results of PPSD with operational data of real power plant. In addition to compare numerical data of PPSD by another numerical data acquired using another two dynamic simulation tools APROS and ASPEN Plus Dynamics to ensure the capability of PPSD to perform such simulations. The model built based on a real power plant design data with all geometry including heat exchangers, turbines, pipes valves, pumps, and control circuits as well. PPSD shows accurate results with high quality in both qualitatively and quantitatively, compared to the measured data and other simulations well. Moreover, it shows that it is capable to perform a dynamic simulation of CCPP with relatively shorter computation time and user-friendly tools.